FAKTOR FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PASIEN HIPERTENSI DALAM MELAKUKAN TERAPI DI PUSKESMAS PANDANARAN KOTA SEMARANG - Amira Noor Sukma; Bagoes Widjanarko; Emmy Riyanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Hypertension is a condition where somebody’s blood pressure in artery, is over 140 mmHg (systolic) and over 90 mmHg (diastolic). The purpose of this research is to get to know about the factors that are related to patient of hypertension’s obedience to do therapy in Puskesmas Pandanaran Semarang. This is a descriptive-analytic research, with cross sectional approach and using simple random sampling so that there are 90 respondents. The results of this research are showing that there are relations between education level (p=0,008), knowledge (p=0,007), belief (p=0,017), motivation (p=0,04), and family support (p=0,006) with patient’s obedience. And there are no relations between age (p=0,129), gender (p=0,309), job (p=0,063), health workers support (p=0,528), and access to health services (p=1,0) with patient’s obedience. The conclusion is that the factors that are related to patient of hypertension’s obedience to do therapy in Puskesmas Pandanaran Semarang are education level, knowledge, belief, motivation, and family support.